2021
DOI: 10.21203/rs.3.rs-475708/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Financial Incentives for Preventing Postpartum Return to Smoking (Fipps): Study Protocol for a Three-Arm Randomised Controlled Trial

Abstract: BackgroundFinancial incentives are an effective way of helping women to stop smoking during pregnancy. Unfortunately, most women who stop smoking at this time return to smoking within 12 months of the infant’s birth. There is no evidence for interventions that are effective at preventing postpartum smoking relapse. Financial incentives provided after the birth may help women to sustain cessation. This randomised controlled trial will assess the effectiveness and cost effectiveness of financial incentives to he… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…44 unanswered questions and future research Many studies have shown a rapid return to smoking post partum, suggesting the use of continued incentive payments post partum to prevent relapse (subject of an ongoing trial, ISRCTN5521821). 19 The current trial shows a clinically important 45 46 increase in birth weight among participants who adhered to their treatment allocation (0.31 kg (95% confidence interval −0.18 to 0.80 kg); 10% of birthweight), similar to the feasibility trial 37 (0.15 kg (−0.62 to 0.80 kg); 5% of birthweight) and to application of average causal effect analysis to the French trial 43 (0.52 kg; 15% of birthweight). A meta-analysis of these and other relevant data would allow a definitive answer to be reached regarding an important birthweight increase 45 46 among those participants who quit smoking with the offer of financial incentives but would not have quit without that offer.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…44 unanswered questions and future research Many studies have shown a rapid return to smoking post partum, suggesting the use of continued incentive payments post partum to prevent relapse (subject of an ongoing trial, ISRCTN5521821). 19 The current trial shows a clinically important 45 46 increase in birth weight among participants who adhered to their treatment allocation (0.31 kg (95% confidence interval −0.18 to 0.80 kg); 10% of birthweight), similar to the feasibility trial 37 (0.15 kg (−0.62 to 0.80 kg); 5% of birthweight) and to application of average causal effect analysis to the French trial 43 (0.52 kg; 15% of birthweight). A meta-analysis of these and other relevant data would allow a definitive answer to be reached regarding an important birthweight increase 45 46 among those participants who quit smoking with the offer of financial incentives but would not have quit without that offer.…”
Section: Policy Implicationsmentioning
confidence: 99%